The Stein Birch-Bark collection in Oxford: thirty years of developing treatment options for our most fragile manuscripts - Gilroy, N (Allied Publishers, 2008)
Treatments for making birch-bark safe to handle range from the minimal to the extremely interventive. The choice of treatment for any object of historical or cultural significance must reflect its artifactual value, uniqueness and the accessibility of the information it holds; this is especially the case with birch-bark as most treatments are difficult or impossible to reverse. In this paper I discuss the treatments used over several decades by institutions both in Europe and Asia, and evaluate the appropriateness of these options for the manuscripts at the Bodleian Library in Oxford. I discuss the development of treatments and changing approaches over the years, and describe the technique I chose for minor repairs, demonstrating that levels of access must determine the choice of treatment.